The reality of the application of educational supervisors Modern technology programs in educational supervision in Sabya Education Department - Al-Hajri, Abdul Aziz Saeed; Gobry, Mohammed Abbas (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to uncover the reality of the educational supervisors ’application of modern technology programs in educational supervision in the Sabya Education Administration. The research used the descriptive approach, and a questionnaire was applied on a sample of supervisors and supervisors in a boy’s education department amounting to (342) members. The research resulted in a number of results, including: The approval of the research sample, with a "large" degree, regarding the application of the educational supervisors at the Sabia Education Department of the Nur system; And the application of the virtual classroom program, and the absence of statistically significant differences at the function level (0.05≥α) between the averages of the responses of the individuals of the research sample on the application of the educational supervisors in the Department of Education in Sabya to the application of (Noor system, and virtual classes) in the educational supervision in the Department of Education in Sabya according to gender variables (Male, female)، Specialization (theoretical, scientific)، In light of these results, the research concluded the construction of a proposed training program to qualify the educational supervisors to apply modern technology programs in educational supervision in the Department of Sabya Education, and it consisted of a number of elements, namely: evidence of justification, philosophy, importance, general objective and objectives of the program in detail, foundations and criteria for designing the program The trainer's specifications, program management, training methods used, mechanisms of its success, implementation strategies, program evaluation, design of the training program and its content, and program evaluation; The researchers also recommended a number of recommendations, including: the involvement of educational supervisors and supervisors to participate in developing training plans for them in light of their actual needs to benefit from their experiences, cooperation between the Training Department of the Department of Education in Sabya and community training institutions to benefit from their experiences in this field.
Keywords: Noor system; virtual classrooms; Modern technology programs